2012
DOI: 10.1620/tjem.228.247
|View full text |Cite
|
Sign up to set email alerts
|

Production of Nitric Oxide Is Lower in Shiga Toxin-Stimulated Neutrophils of Infants Compared to Those of Children or Adults

Abstract: Hemolytic uremic syndrome (HUS) in infants is mainly caused by the Shiga toxin (Stx), which is produced by pathogenic Escherichia coli O157:H7. Infants are prone to develop HUS in comparison to older children and adults, but its underlying mechanism remains unknown. Recent observations suggest that reactive oxygen species (ROS) and reactive nitrogen species (RNS) including nitric oxide (NO) may be involved in the pathogenesis of HUS. We therefore measured NO production by neutrophils prepared from infants (6-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The large differences in transcriptome between neutrophils from patients with active systemic‐onset JIA and neutrophils from healthy controls, in combination with the overlap with the transcriptome of other systemic inflammatory conditions, point toward the notion that there is a similar primed phenotype of neutrophils that cannot be attributed to differences in age or other confounding factors. This is supported by other studies that have shown no differences in neutrophil function between healthy children and adults .…”
Section: Discussionsupporting
confidence: 89%
“…The large differences in transcriptome between neutrophils from patients with active systemic‐onset JIA and neutrophils from healthy controls, in combination with the overlap with the transcriptome of other systemic inflammatory conditions, point toward the notion that there is a similar primed phenotype of neutrophils that cannot be attributed to differences in age or other confounding factors. This is supported by other studies that have shown no differences in neutrophil function between healthy children and adults .…”
Section: Discussionsupporting
confidence: 89%
“…In two recent large outbreaks, women developed HUS in disproportionate numbers (9,13). Studies that address why children are more likely than adults to develop HUS suggest that a difference in complement activation (14,15), platelet activation (16), or in nitric oxide production (17) may explain the disparity.…”
mentioning
confidence: 99%
“…Similar results were reported by Tsui et al . 18 who found lower Shiga toxin-stimulated intracellular neutrophil NO generation accompanied by impaired NOS2 mRNA expression in infants compared with older children and adults. In line with their findings, in the present study unstimulated intracellular NO generation was comparable between CB and adult neutrophils, possibly due to low basal NO production 18 .…”
Section: Discussionmentioning
confidence: 99%
“…18 who found lower Shiga toxin-stimulated intracellular neutrophil NO generation accompanied by impaired NOS2 mRNA expression in infants compared with older children and adults. In line with their findings, in the present study unstimulated intracellular NO generation was comparable between CB and adult neutrophils, possibly due to low basal NO production 18 . As an alternative to the NOS-dependent mechanism, which, in adults, is responsible for approximately two-thirds of neutrophil NO production, another possible source of NO may be a non-enzymatic reaction between H 2 O 2 and arginine 9,19 .…”
Section: Discussionmentioning
confidence: 99%